Longitudinal mentorship to support the development of medical students’ future professional role: a qualitative study - Kalén, Susanne (BMC Med Educ, 2015)
BACKGROUND: Mentoring has been employed in medical education in recent years, but there is extensive variation in the published literature concerning the goals of mentoring and the role of the mentor. Therefore, there is still a need for a deeper understanding of the meaning of mentoring for medical students’ learning and development. The aim of this qualitative study is to explore how formal and longitudinal mentoring can contribute to medical students’ professional development. METHODS: Sixteen medical students at a Swedish university were interviewed individually about their experiences of combined group and one-to-one mentoring that is given throughout their studies. The mentoring programme was focused on the non-medical skills of the profession and used CanMEDS roles of a physician for students’ self-assessment. Data were analysed using a latent, interpretive approach to content analysis. RESULTS: The results comprise three themes: Integrating oneself with one’s future role as a physician, Experiencing clinical reality with the mentor creates incentives to learn and Towards understanding the professional competence of a physician. The mentorship enabled the students to create a view of their future professional role and to integrate it with their own personalities. The students’ understanding of professional competence and behaviour evolved during the mentorship and they made advances towards understanding the wholeness of the profession. This approach to mentorship supported different components of the students’ professional development; the themes Integrating oneself with one’s future role and Towards understanding the professional competence of a physician can be regarded as two parallel processes, while the third theme, Experiencing clinical reality with the mentor creates incentives to learn, promotes these processes. CONCLUSIONS: Formalized and longitudinal mentoring focusing on the non-medical skills can be recommended to help medical students to integrate their professional role with themselves as individuals and promote understanding of professional competence in the process of becoming a physician.